Large‐scale deep multi‐layer analysis of Alzheimer's disease brain reveals strong proteomic disease‐related changes not observed at the RNA level. (December 2021) - Johnson, Erik C.B.; Carter, Emma Kathleen; Dammer, Eric B; Duong, Duc M; Liu, Yue; Liu, Jiaqi; Betarbet, Ranjita; Ping, Lingyan; Yin, Luming; Beach, Thomas G; Peng, Junmin; Gaiteri, Chris; et al.
Abstract: Background: The biological processes that are disrupted in the Alzheimer's disease (AD) brain remain incompletely understood. We recently performed a proteomic analysis of >2000 brains to better understand these changes, which highlighted alterations in astrocytes and microglia as likely key drivers of disease. Method: Here, we extend this analysis by analyzing >1000 brain tissues using a tandem mass tag mass spectrometry (TMT‐MS) pipeline, which allowed us to nearly triple the number of quantified proteins across cases. We analyzed this deeper dataset using protein co‐expression network analysis to identify biological processes altered in AD. Result: We identified new protein co‐expression modules that were highly preserved across cohorts and brain regions, and strongly altered in AD. Nearly half of the protein co‐expression modules, including modules significantly altered in AD, were not observed in RNA networks from the same cohorts and brain regions, highlighting the proteopathic nature of AD. Two such AD‐associated modules unique to the proteomic network included a module related to MAPK signaling and metabolism, and a module related to the matrisome. Analysis of paired genetic and proteomic data within subjects showed that expression level of the matrisome module was influenced by the ApoE4 genotype, but was not related to the rate of cognitive decline after adjustment for neuropathology. In contrast, the MAPK/metabolism module was strongly associated with the rate of cognitive decline after adjustment for neuropathology. Conclusion: Disease‐associated modules unique to the proteome are sources of promising therapeutic targets and biomarkers for AD.